Análisis de la formalización en Colombia ante la llegada del régimen simple de tributación - Gonzalez Perez, Nicolle Alejandra (Universidad Antonio Nariño, 2024)
The simple taxation regime is born with the idea of closing the tax gap and reducing levels of informality in the country. On one hand, there are factors that prevent these levels from decreasing, such as the negative perception regarding high tax rates and the complexity of filing various types of declarations. Within the regime, benefits are identified to help change this perception and achieve increased formalization, through rate reductions and the elimination of obligations such as sales tax for certain economic groups, among others.